Fear and Loathing in Britain: A Framing Analysis of News Coverage during the Foot and Mouth Disease Outbreaks in the United States - Karen J. Cannon; Tracy A. Irani (Journal of Applied Communications, 2011)
Communicating science is a complex task filled with challenges for scientists and communicators. In the field of agricultural communications, some of the most complex and controversial topics covered in today’s media are related to contagious animal diseases. The purpose of this study was to explore the use of frames in two daily newspapers, The New York Times in the U.S., and The Guardian in the U.K., during both the 2001 and 2007 outbreaks of foot and mouth disease (FMD) in Britain. The analysis showed that the primary frame used in articles published during the outbreaks was fear, followed closely by a connection of FMD to bovine spongiform encephalopathy (BSE, or mad cow disease) and the potential for human infection. Secondary frames included criticism of government and politics, and a military/war frame. This research shows that the use of frames in media has the potential to create unnecessary fear among consumers who already possess low levels of knowledge regarding agricultural production practices. Future research in this area should include an evaluation of headlines corresponding to newspaper articles, as well as a study of the sources of information and quotations used in such stories. Through the use of such framing analyses, agricultural communications scholars can begin to take a concrete step in exploring the ways in which the public interprets, creates meaning and values information related to agriculture.
Keywords: communication; animal diseases; agricultural; challenges; framing